Direct Initiation of Long-Acting Cabotegravir Plus Rilpivirine in People with HIV and Suboptimal Virologic Suppression: A Randomized Trial - Nan-Yu Chen; Cheng-Pin Chen; Yi-Chun Lin; Shu-Hsing Cheng; Shien-Shian Huang; Jun-Yuan Zheng; Ching-Tai Huang; Ting-Shu Wu; Ting-Yi Su; Shian-Sen Shie; Jung-Jr Ye; Chun-Fu Yeh; et al. (Clinical Infectious Diseases, 2026)
Abstract Background Long-acting injectable cabotegravir plus rilpivirine (LA CAB+RPV) is approved for virally suppressed people with human immunodeficiency virus (HIV), but evidence for its use in those with persistent viremia and adherence challenges remains limited. Methods We conducted a multicenter, open-label, randomized study involving oral antiretroviral therapy (ART)-experienced people with HIV who had been diagnosed with HIV for at least 12 months and a most recent HIV-1 RNA level of at least 200 copies per milliliter. Participants with resistance-associated mutations to CAB or RPV were excluded. Eligible participants were randomly assigned in a 1:1 ratio to receive immediate LA CAB+RPV or to continue standard oral therapy until Week 24 (delayed switch group). The primary endpoint was the proportion of participants with an HIV-1 RNA level of less than 200 copies per milliliter at Week 24. Results Of 61 randomized participants, 45 met eligibility criteria and were included in the analysis; 91% were male, and the median baseline HIV-1 RNA was 35,000 copies/mL. At Week 24, viral suppression was achieved in 88.0% (22/25) in the immediate LA group versus 55.0% (11/20) in the delayed switch group (relative risk for failure to achieve viral suppression, 0.27; 95% CI, 0.08–0.86; p = 0.026). The effect of LA CAB+RPV was sustained through Week 52. Conclusions Among people with HIV and viremia associated with adherence challenges, immediate initiation of LA CAB+RPV resulted in higher rates of viral suppression than continued oral ART, supporting its use beyond populations with stable suppression.